Some Investigations and Application of Acoustics in Geophysics - FA Lin; YANG Huiting; MENG Shuangshuang; FANG Xiangrong; FAN Jin; ZHANG Kaiqiang; XU Yulin; ZOU Xiao; CUI Xinhao; SHI Guiquan; ZHAO Meishan (Cejing jishu)
We provide an overview of recent research advancements in the field of geoacoustics, with a focus on novel discoveries. We explore, analyze and discuss new physical phenomena, such as the reflection and refraction of acoustic waves at interfaces between anisotropic rocks and liquids, the characteristics of piezoelectric transducers in terms of electric-acoustic and acoustic-electric conversion, the generation of intrinsic noise, and the physical mechanism of acoustic wave propagation in viscous media. We present new physical models and algorithms with fresh theoretical formulations and discuss the possibility of abnormal incidence angle, acoustic attenuation, and acoustic Goos-Hänchen effect. We also discuss a method of formation reflection coefficient inversion using logging and seismic data, taking into account rock anisotropy and dip angle. Furthermore, we delve into the physical mechanism and potential applications of intrinsic noise in viscous solid media and introduce a parallel transmission network that describes the electric-acoustic and acoustic-electric conversion characteristics of piezoelectric transducers. We present the newly established parallel/series lumped vibrational transmission network, the acoustic measurement process, and the applications of the Kaiser effect in petroleum engineering.